Energy dispatch optimization of islanded multi-microgrids based on symbiotic organisms search and improved multi-agent consensus algorithm. (15th January 2022) - Yang, Kang; Li, Chunhua; Jing, Xu; Zhu, Zhiyu; Wang, Yuting; Ma, Haodong; Zhang, Yu
Abstract: To improve the utilization rate of renewable energy resources (RES) and solve energy dispatch optimization of islanded multi-microgrids (MMG), a phased algorithm based on symbiotic organisms search (SOS) and an improved multi-agent (MA) consensus algorithm (IMACA) is proposed. The structure of islanded MMG based on the MA system is established and community MG is added to make full use of RES. The algorithm including two phases is established: Maximum consumption of RES based on SOS in Phase 1 is used to redistribute the shiftable load in time and space to reduce the residual RES; Energy dispatch optimization based on IMACA in Phase 2 obtains the optimal solution gradually through error adjustment step-size and weight matrix composed of unit cost and introduces artificial operators to improve the global searching ability. The purpose of IMACA is to overcome the problems of inverse solution and the need to clarify the operation cost relationship among each unit in the traditional MA consensus algorithm. Simulation shows that the utilization rate of RES can reach 99.99% when the difference between RES and load is large at some moments, and the output of each unit can be allocated quickly and reasonably to obtain the maximum economic benefit. Highlights: A structure of islanded MMG based on MAS is established. The proposed algorithm can significantly improve the utilization rate of RES. The IMACA can overcome the problems of inverse solution. The ability of islanded MMG to handle uncertainty among PV, WT and load is improved. The global searching ability of IMACA can be improved through the artificial operators.